DRIVE FOR WRITING UTENSIL, ETC. IN X-Y PLOTTER, ETC - TOYODA TSUTOMU; CHIBA KENJI (1989)
PURPOSE: To ensure soft landing of a writing instrument onto a mounting surface through a simple mechanism by releasing the descending speed of the solenoid driven writing instrument using a spring means having approximation characteristics of a several degree curve. CONSTITUTION: Under initial state, a fixed ring 40 faces a resilient body 32 through a specified interval (a). When a solenoid 12 is conducted, a descending force FD for attracting an armature 16 downward is generated. The force FD has reverse proportional attraction curve charactertstics, i.e., the strength of the force FD is proportional reversely to the interval between the upper attraction face of the solenoid 12 and the armature 16. Descending speed of the armature is accelerated when the resilient body 32, 34 is not present and a writing instrument 22 held by an arm 18 is also accelerated and begins to descend, but the ascending force of the resilient body 32, 34 acts stepwise on a working shaft 14 to follow the attraction curve characteristics thus keeping a constant descending speed of the armature 16. Consequently, lower end of the writing instrument 22 lands on the surface of a sheet placed on a table 4 with a gentle impact.